The regulation of the profession of Physical Education for a professional category: The case of Minas Gerais - Maria José Carvalho; Gustavo Bavaresco; Edson Oliveira; Marisa Sousa; Gustavo Paipe; Cláudio Bosch (Universidade Salgado de Oliveira, 2021)
The aim of the present study was to characterize the evolution of the process of regulation of Physical Education profession and its representation from the perspective of the Counselors of the CONFEF / CREF6 / MG System, in the state of Minas Gerais. It used a qualitative analysis with the application of interviews, as well as the interpretation of legal documents. The main results were divided into 4 categories: i) From the Physical Education Teachers Associations (APEFs) to the regulation of the Physical Education profession; ii) Teaching Physical Education and Sport in School; iii) Physical Activity and Health; iv) Sports Training; v) Sport Management. We can understand within the proposed categories that the Councilors perceive an improvement in the quality of Physical Education and Sports from the regulation of this profession.